Communicable Diseases Intelligence volume 11 issue 3 - 16 February 1987 - whole issue - No author listed, (Communicable Diseases Intelligence, 1987)
Whole-issue pdf, comprising: Virus Reporting Scheme Articles Typhoid outbreak - Mount Hagen (Papua New Guinea) The influence of immunity on raw milk-associated Campylobacter infection Vaccine related poliomyelitis in non-immunised relatives and household contacts [U.K.] Imported poliomyelitis - implications for travellers to third world countries Publication Notice Draft "Clinical handbook epidemic polyarthritis" - Australia Australia - Communicable Diseases Intelligence Reporting Period 19-07-1987 to 08-02-1987 Notifiable Diseases reported in Australia Period 10 - 6 September 1986 to 3 October 1986